Associations of triglyceride-glucose index with N-terminal pro-B-type natriuretic peptide and mortality in middle-aged and elderly individuals - Xie, Haitao; Shen, Le; Li, Jianghong; Lv, Chuxin; Sun, Tong; Yu, Peng; Chen, Xiaohu; Tang, Shuhua (Frontiers in Endocrinology, 2025)
BackgroundThe triglyceride-glucose (TYG) index is a simple marker for insulin resistance (IR). However, its relationship with elevated NT-proBNP levels is not well understood in middle-aged and elderly individuals without known cardiovascular diseases (CVD).MethodsThe study cohort data were derived from National Health and Nutrition Examination Survey (NHANES) and inpatients of the Department of Cardiology at Jiangsu Provincial Hospital of Traditional Chinese Medicine (JSHTCM). Multivariable logistic regression was employed to assess the relationship between the TYG index and elevated NT-proBNP. Multivariable Cox proportional hazards models were used to estimate the adjusted risk ratio of the TYG index for all-cause mortality. Furthermore, restricted cubic spline (RCS) plots were generated to visually represent the linear or non-linear relationships between the TYG index and elevated NT-proBNP as well as all-cause mortality.ResultsThe age-standardized prevalence of elevated NT-proBNP among middle-aged and elderly individuals was 29.21% in females and 17.08% in males. A negative correlation was observed between the TYG index and elevated NT-proBNP, study cohort 1: [T3 vs T1: OR (95% CI): 0.73 (0.55, 0.96), p for trend= 0.027]; study cohort 2: [β (95% CI): -37.58 (-59.11, -16.06), p for trend=0.002]. Each unit increase in the TYG index is correlated with a 25% increase in the adjusted risk of all-cause mortality [HR (95% CI): 1.25 (1.08, 1.44), p=0.003]. The RCS plots supported the multivariate regression model findings.ConclusionsThe TYG index level is negatively correlated with the incidence of elevated NT-proBNP and is associated with all-cause mortality, regardless of the presence of elevated NT-proBNP.